Correlation of dynamic contrast‐enhanced MRI perfusion parameters with angiogenesis and biologic aggressiveness of rectal cancer: Preliminary results. Issue 2 (21st December 2013) - Yeo, Dong‐Myung; Oh, Soon Nam; Jung, Chan‐Kwon; Lee, Myung Ah; Oh, Seong Taek; Rha, Sung Eun; Jung, Seung Eun; Byun, Jae Young; Gall, Peter; Son, Yohan
<x xml:space="preserve">Abstract</x> Purpose To investigate whether quantitative parameters derived from dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) are correlated with angiogenesis and biologic aggressiveness of rectal cancer. Materials and Methods A total of 46 patients with rectal cancer underwent DCE‐MRI. Using a two‐compartmental model, quantitative parameters (Ktrans, kep, ve, and iAUC) were calculated from the whole‐transverse region of interest (ROI) and high Ktrans area ROI of entire tumors. Histological specimens were analyzed for tumor size; T/N stage; lymphatic, vascular, perineural invasion; expression of epidermal growth factor receptor (EGFR); and KRAS gene mutations. Tumor angiogenesis was evaluated based on the microvessel density (MVD) and the expression level of the vascular endothelial growth factor. Correlations of the DCE‐MRI parameters with histological markers and angiogenesis were determined using Student's t‐test and analysis of variance (ANOVA). Results The mean kep from high Ktrans area ROIs showed a significantly positive correlation with MVD (P = 0.030, r = 0.514, R2 = 0.264). The mean kep from the whole‐transverse ROIs showed a significant inverse correlation with T stage (T1 vs. T2–4, P = 0.021). EGFR‐positive cancer displayed higher mean Ktrans (P = 0.045) and kep (P = 0.038) than EGFR‐negative cancer in whole‐transverse ROIs. Conclusion These preliminary results suggest that the determination of kep of high Ktrans area permits the noninvasive estimation of tumor angiogenesis in rectal cancer and that DCE‐MRI parameters can be used as imaging biomarkers to predict the biologic aggressiveness of the tumor and patient prognosis. J. Magn. Reson. Imaging 2015;41:474–480.© 2013 Wiley Periodicals, Inc.